THE SCIENCE FAIR AS AN INNOVATIVE STRATEGY FOR TEACHING AND MEANINGFUL LEARNING - Pereira , Marta da Silva; Pereira , Eliaquim Barbosa (Editora Impacto Científico, 2025)
The general objective of this study is to analyze the importance of Science Fairs as an innovative teaching strategy capable of promoting meaningful learning. The specific objectives are to understand the roles of teachers and students in this process; to identify the pedagogical and social benefits resulting from participation in Science Fairs; and to discuss the challenges faced in effectively implementing this methodology in the context of basic education. This is an integrative literature review. Data collection was carried out in the SciELO and Google Scholar databases using the keywords: “Science Fair,” “meaningful learning,” “interdisciplinarity,” and “scientific literacy” between 2020 and 2025. The results of the research show that Science Fairs play an essential role in the educational process, functioning as spaces for integrating theoretical knowledge and investigative practice. It was found that Science Fairs also contribute to citizenship education by encouraging ethical, cooperative, and sustainable attitudes. The studies analyzed indicate that, by investigating real problems and proposing solutions, students better understand the role of science in society and the importance of social responsibility. Furthermore, the interdisciplinarity of the fairs enables dialogue among different areas of knowledge, promoting contextualized learning connected to everyday life. Future research is recommended to explore new approaches, such as the use of digital technologies and the impact of these activities on inclusive and environmental education. Thus, science fairs remain fundamental pedagogical practices for strengthening scientific culture and fostering students’ holistic development.DOI: https://doi.org/10.56238/edimpacto2025.092-040